Leveraging collaboration: script development processes in low budget Australian feature filmmaking. Issue 3 (2nd September 2021) - Cake, Susan; Maher, Sean; McGrath, Tony
ABSTRACT: For independent Australian filmmakers working outside traditional funding sources, the script often provides the sole means of raising finance to take the film into production. In the case of the low budget Australian feature films Pimped ([2018], "Directed by David Barker. Playground Films." Apple TV) and Watch the Sunset ([2017], "Directed by Tristan Barr and Michael Gosden." Barr Lipp Productions. STAN), however, script development was elevated and sustained by the filmmakers resisting a rigid adherence to writing, directing, and producing roles and opening up input from actors. This research employs case study analysis supported by interviews with the writers/director of Pimped and co-writer of Watch the Sunset to examine the script development processes that led to the successful completion and distribution of two low budget Australian feature films. Born out of the necessity to self-fund development, Pimped and Watch the Sunset provide insight into script development processes that value flexibility and receptiveness to the contributions of creative practitioners traditionally divided by above and below-the-line roles and exemplify how creative collaboration can facilitate successful development of low budget films operating beyond the constraints of screen funding bodies.